A longitudinal investigation of Aβ, anxiety, depression, and mild cognitive impairment - Pink, Anna; Krell-Roesch, Janina; Syrjanen, Jeremy A; Vassilaki, Maria; Lowe, Val J; Vemuri, Prashanthi; Stokin, Gorazd B; Christianson, Teresa J; Kremers, Walter K; Jack, Clifford R; Knopman, David S; Petersen, Ronald C; et al. (Alzheimer's & dementia, 2022)
INTRODUCTION: We investigated the longitudinal relationship between cortical amyloid deposition, anxiety, and depression and the risk of incident mild cognitive impairment (MCI). METHODS: We followed 1440 community-dwelling, cognitively unimpaired individuals aged ≥ 50 years for a median of 5.5 years. Clinical anxiety and depression were assessed using Beck Anxiety and Depression Inventories (BAI, BDI-II). Cortical amyloid beta (Aβ) was measured by Pittsburgh compound B positron emission tomography (PiB-PET) and elevated deposition (PiB+) was defined as standardized uptake value ratio ≥ 1.48. We calculated Cox proportional hazards models with age as the time scale, adjusted for sex, education, and medical comorbidity. RESULTS: Cortical Aβ deposition (PiB+) independent of anxiety (BAI ≥ 10) or depression (BDI-II ≥ 13) increased the risk of MCI. There was a significant additive interaction between PiB+ and anxiety (joint effect hazard ratio 6.77; 95% confidence interval 3.58-12.79; P = .031) that is, being PiB+ and having anxiety further amplified the risk of MCI. DISCUSSION: Anxiety modified the association between PiB+ and incident MCI.
Keywords: Cognitive Dysfunction; deprese; depression; Positron-Emission Tomography; lidé; Depression; amyloid imaging; anxiety; Alzheimer Disease; mozek; aniliny; amyloidní beta-protein; Brain; mild cognitive impairment; neuropsychologické testy; Humans; úzkost; Aniline Compounds; pozitronová emisní tomografie; Anxiety; kognitivní dysfunkce; Alzheimerova nemoc; Amyloid beta-Peptides; Neuropsychological Tests; Pittsburgh compound B positron emission tomography